2014
DOI: 10.1246/cl.131232
|View full text |Cite
|
Sign up to set email alerts
|

Size- and Structure-specificity in Catalysis by Gold Clusters

Abstract: Although gold in bulk is poorly active as a catalyst, it exhibits surprisingly high catalytic activity when deposited as nanoparticles (NPs) on base metal oxides. The catalytic performance of supported gold NPs can be created by choosing the kind of support materials, by controlling the size of gold, and by building up strong contact of gold with the supports. Since perimeter interfaces around gold NPs act, in principle, as the active sites for oxidation and hydrogenation, gold should be smaller than 10 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 63 publications
4
146
0
3
Order By: Relevance
“…Since then, Au has attracted growing attention as a catalyst and become the preeminent example of a size effect in heterogeneous catalysis. [9][10][11] As CO oxidation is one of the simplest reactions which Au can catalyse, and CO is frequently used as a probe molecule in surface science, CO oxidation on TiO 2 supported Au nanoparticles has become a prototypical model system in Au catalysis, [12][13][14][15] and numerous studies have been reported regarding the reaction mechanisms, [16][17][18] active sites, 11,[19][20][21] and active species. 22,23 Looking at the experimentally measured catalytic activities of Au nanoparticles on different supports in the CO oxidation reaction, two main conclusions can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, Au has attracted growing attention as a catalyst and become the preeminent example of a size effect in heterogeneous catalysis. [9][10][11] As CO oxidation is one of the simplest reactions which Au can catalyse, and CO is frequently used as a probe molecule in surface science, CO oxidation on TiO 2 supported Au nanoparticles has become a prototypical model system in Au catalysis, [12][13][14][15] and numerous studies have been reported regarding the reaction mechanisms, [16][17][18] active sites, 11,[19][20][21] and active species. 22,23 Looking at the experimentally measured catalytic activities of Au nanoparticles on different supports in the CO oxidation reaction, two main conclusions can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] It has been reported that Au NPs with diameter from 1.0 nm to 5.0 nm exhibits surprisingly high activity and selectivity for several reactions. 16,19,21,22 Thus, there are large expectations that TM NPs supported on oxides can improve the breaking of the strong C−C σ bond and to reduce the number of undesirable intermediate compounds, [1][2][3]14 which present a great challenge for ethanol SRR catalysts. Platinum (Pt) NPs of about 3 nm supported on carbon black have been studied, 9,10,23 as well as combined with SnO 2 , 10 however, acid acetic is one of the predominant undesirable products.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, colloidal gold nanoparticles (NPs) have gained tremendous attention as catalysts for organic reactions such as selective oxidation, hydrogenation, and carbonAcarbon coupling reactions due to the robust and green nature of gold catalysts [10][11][12][13][14][15][16]. According to a previous work by Lambert et al, oxide-supported gold nanoparticles are active catalysts for Sonogashira cross-coupling reactions between iodobenzene (IB) and phenylacetylene (PA) [17].…”
Section: Introductionmentioning
confidence: 99%